Glucose-induced changes in somatostatin-14 and somatostatin-28 released from rat hypothalamic fragments 'in vitro'. - Lengyel, A; Nieuwenhuyzen Kruseman, A; Grossman, A; Rees, L; Besser, G (1984)
Previous data suggest that somatostatin is present and released from the hypothalamus in several molecular forms, basally and after K+ or electrical stimulation. In order to evaluate the proportions of somatostatin-14 (S14) and somatostatin-28 (S28) released during a stimulus which may be more closely related to the control of growth hormone secretion 'in vivo', we studied the molecular forms of somatostatin released from hypothalamic fragments ' in vitro', during incubations with different glucose concentrations (1.35 and 22mM), which we have previously shown to be inversely related to somatostatin release. Sephadex G-50 chromatography demonstrated that both forms are released in the same proportions (S14: 70%; S28: 30%) during incubation with different glucose concentrations; there is a parallel increase in both forms when low glucose is used. Although on a molar basis less S28 is released than S14, the higher potency, longer duration of action and higher affinity for pituitary receptors of S28 suggests that it may be of major physiological importance.